2017
DOI: 10.1002/lt.24799
|View full text |Cite
|
Sign up to set email alerts
|

The donor risk index: A decade of experience

Abstract: In 2006, derivation of the donor risk index (DRI) highlighted the importance of donor factors for successful liver transplantation. Over the last decade, the DRI has served as a useful metric of donor quality and has enhanced our understanding of donor factors and their impact upon recipients with hepatitis C virus, those with low Model for End-Stage Liver Disease (MELD) score, and individuals undergoing retransplantation. DRI has provided the transplant community with a common language for describing donor or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 85 publications
1
64
1
3
Order By: Relevance
“…However, it has been well-validated to guide organ allocation policy and to identify patients who are at risk of death because of end-stage liver disease [11] . In general, organs with a high donor risk index (DRI) should be transplanted into patients with a low MELD score of 10-14 [12,13] . However, subsequent data showed that patients with high MELD scores could also bene t from sub-optimal organ transplants [14][15][16] ; therefore, we included the entire range of MELD scores into our model.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been well-validated to guide organ allocation policy and to identify patients who are at risk of death because of end-stage liver disease [11] . In general, organs with a high donor risk index (DRI) should be transplanted into patients with a low MELD score of 10-14 [12,13] . However, subsequent data showed that patients with high MELD scores could also bene t from sub-optimal organ transplants [14][15][16] ; therefore, we included the entire range of MELD scores into our model.…”
Section: Discussionmentioning
confidence: 99%
“…Although marginal allograft, such as severe steatosis and extended ischemia time, might influence the postoperative morbidity and mortality in deceased donors, in the present study, we used exclusively donor age and graft volume as donor variables. In the majority of cases, allograft qualities such as cold ischemic time, steatosis, and fibrosis were sufficient and not marginal as a result of the nature of LDLT, which represented the majority of LT in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative clinical course after LT should be determined by preoperative/postoperative recipient conditions and donor allograft conditions. Many studies have investigated the preoperative and intraoperative risk factors of recipient‐related or allograft‐related DDLT and LDLT recipients . However, to our knowledge, a large population study investigating both recipient and donor allograft conditions based on registry data has not been carried out to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, this model has many limitations, such as an inability to assess the degree of injury that is caused by the process of graft procurement or cold preservation and reperfusion. Also, it is applicable to the US donor population but is not readily transferable to populations in other countries . In order to face the limitations of DRI, novel statistical models have been developed, such as the UK donor liver index and the balance of risk (BAR) score.…”
Section: Methodology and Literature Researchmentioning
confidence: 99%